Pengaruh Penggunaan Gadget dan Media Sosial terhadap Perilaku Sosial dan Karakter Anak Sekolah Dasar - Mareta Wahyu Delistya; Sonya Woro Setyaningrum; Fitri Suci Susiyowati; Bunga Cantika Ramadhani; Annisa Meta Nur Alifia (Universitas PGRI Madiun, 2026)
The rapid development of digital technology has significantly changed the patterns of interaction and social behavior of elementary school children. Gadgets and social media platforms, such as TikTok, have become an integral part of children's daily lives, serving as tools for entertainment, communication, and learning. This study aims to examine the influence of gadget and social media use on children's social behavior and character development, as well as to identify the efforts that parents, teachers, and schools can make to minimize their negative impacts. This research employed a library research method with a qualitative descriptive approach by analyzing relevant literature and previous studies related to the use of gadgets, social media, and the digital environment among elementary school children. The findings indicate that the use of gadgets and social media has both positive and negative effects. On the one hand, digital technology facilitates communication, supports the learning process, broadens children's knowledge, and enhances their creativity. On the other hand, excessive and uncontrolled use may reduce direct social interaction, decrease physical activity, lead to gadget dependency, and negatively affect children's discipline, empathy, and social awareness. Therefore, the active involvement of parents, teachers, and schools is essential through proper supervision, screen time management, positive role modeling, and the strengthening of character education and digital literacy. In conclusion, the impact of gadgets and social media on children depends not only on the intensity of their use but also on the guidance and supervision provided by adults in their surrounding environment.